2017
DOI: 10.1038/onc.2017.158
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 demethylates HIF1α to inhibit hydroxylation and ubiquitin-mediated degradation in tumor angiogenesis

Abstract: Lysine-specific demethylase 1 (LSD1), which has been considered as a potential therapeutic target in human cancer, has been known to regulate many biological functions through its non-histone substrates. Although LSD1-induced hypoxia-inducible factor alpha (HIF1α) demethylation has recently been proposed, the effect of LSD1 on the relationship between HIF1α post-translational modifications (PTMs) and HIF1α-induced tumor angiogenesis remains to be elucidated. Here, we identify a new methylation site of the HIF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 42 publications
1
98
0
Order By: Relevance
“…SET7/9-mediated monomethylation of HIF-1α at K32 was later confirmed by Kim et al in vitro and in human cervical carcinoma HeLa cells [46]. SET7/9 also catalyzes dimethylation of HIF-1α at K391 in HEK293T cells [38]. However, these two recent studies showed that SET7/9-mediated HIF-1α methylation decreases HIF-1α protein levels through increasing VHL-HIF-1α interaction and HIF-1α ubiquitination, thereby inhibiting HIF-1 transcriptional activity in transfected cells [38, 46].…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 95%
See 4 more Smart Citations
“…SET7/9-mediated monomethylation of HIF-1α at K32 was later confirmed by Kim et al in vitro and in human cervical carcinoma HeLa cells [46]. SET7/9 also catalyzes dimethylation of HIF-1α at K391 in HEK293T cells [38]. However, these two recent studies showed that SET7/9-mediated HIF-1α methylation decreases HIF-1α protein levels through increasing VHL-HIF-1α interaction and HIF-1α ubiquitination, thereby inhibiting HIF-1 transcriptional activity in transfected cells [38, 46].…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 95%
“…However, ARD1 fails to acetylate HIF-1α in vitro [36, 37]. It was recently suggested that prolyl hydroxylation and K391 methylation are prerequisite for ARD1-mediated K532 acetylation of HIF-1α [38]. …”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 99%
See 3 more Smart Citations